Landscape imprints of haying technology in eastern Idaho and western Montana - Sando, Linnea Christiana (Kansas State University, 2010)
Hayscapes, or haying landscapes, are distinctive cultural landscapes that evolve through time as a result of technological changes in response to economic realities. Since settlement began in the western United States, hay-making has gone through a number of mechanical revolutions that have given rise to an assortment of different methods employed in the process of gathering and storing hay. For this research, the changes in haying technology and resulting cultural landscapes are divided into four eras based on the haying methods of the time in western Montana and eastern Idaho. Common haying technology used in the study area at one time or another includes rudimentary devices, hay derricks, Beaverslides, overshots, swinging arm stackers, small, rectangular balers, tractors with front loader extensions, loaf stackers, round balers, large, rectangular balers, and forage harvesters (choppers). Farmers and ranchers create different hayscapes based on the technology used. There are different reasons for using different haying technologies, such as the type and size of agricultural operation, economics, and personal preference. Landscapes are documents, and by “reading” the haying landscape, we are able to acknowledge the story of the transition of life and ways of the past to present-day living of the people. Insights are discovered regarding past and present technologies and aspects of their social and economic systems. This study examines the different past and present haying landscapes of western Montana and eastern Idaho to better understand reasons and ways in which human activities have imprinted the landscape and given rise to distinct, and aesthetically pleasing, patterns on the earth’s surface.
Keywords: Landscape; Haying; Haying technology; Montana; Idaho; Geography (0366)